PERANGKAT PEMBELAJARAN IPA BERPOLA PBMP DIPADU SCIENTIFIC APPROACH TERINTEGRASI NILAI ISLAMI UNTUK BERPIKIR KRITIS DAN METAKOGNISI SISWA SEKOLAH/MADRASAH MULTIETNIS - Ade Haerullah; Said Hasan; Muhktar Yusuf (Universitas Khairun, 2019)
This study aims to determine the potential of learning models with the Pattern of Empowerment Thinking Through Questions (PBMP) combined with integrated scientific approach integrated Islamic values in empowering critical thinking and metacognition of elementary school students or madrasah ibtidaiyah. Furthermore, this study aimed to determine differences in critical thinking and metacognition of students with different ethnicities related to the learning model applied. This research is classified as a quasi experiment, conducted in the 2018/2019 school year in class V at two Ibtidaiyah Madrasahs classified as schools or multiethnic Madrasas in Ternate City. The measured variables in this study were students' critical thinking skills and metacognition. To test the hypotheses, Anakova in the SPSS 16.0 program was used. If the probability value is significant, then further tests with LSD. The results of data analysis show that PBMP learning combined with integrated scientific approach integrated Islamic values has an effect on students 'critical thinking and metacognition and or it can be said that PBMP patterned learning combined with an integrated scientific approach integrated Islamic values is more empowering students' critical thinking and metacognition than conventional models. There are differences in students' critical thinking between ethnic groups in the class applied to the model, these differences can be concluded that students in each ethnic group have different learning styles. Keywords: multiethnic, PBMP, scientific approach, Islamic values, Metacognition, critical thinking.